2022
DOI: 10.1002/ajmg.a.63009
|View full text |Cite
|
Sign up to set email alerts
|

A multicenter study to evaluate pain characteristics in osteogenesis imperfecta

Abstract: The objective was to describe pain characteristics and treatments used in individuals with varying severity of osteogenesis imperfecta (OI) and investigate pain‐associated variables. This work was derived from a multicenter, longitudinal, observational, natural history study of OI conducted at 12 clinical sites of the NIH Rare Diseases Clinical Research Network's Brittle Bone Disorders Consortium. Children and adults with a clinical, biochemical, or molecular diagnosis of OI were enrolled in the study. We did … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
6
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 48 publications
1
6
0
Order By: Relevance
“…Results from this study noted a correlation between intensity of pain and age, weight and BMI. People who were older, or presented with increased weight and higher BMI, reported a higher intensity of pain, these results were similar to those published by Rodriguez Celin et al in a large population of individual with OI (Rodriguez Celin et al, 2023).…”
Section: Discussionsupporting
confidence: 90%
See 4 more Smart Citations
“…Results from this study noted a correlation between intensity of pain and age, weight and BMI. People who were older, or presented with increased weight and higher BMI, reported a higher intensity of pain, these results were similar to those published by Rodriguez Celin et al in a large population of individual with OI (Rodriguez Celin et al, 2023).…”
Section: Discussionsupporting
confidence: 90%
“…More than 60% of people with OI in our population reported pain, with more adults (80%) reporting pain compared with children (55%). Previous authors have reported pain ranging from 30% to 87% of children and adults with OI (Arponen et al, 2018; Fano et al, 2010; Fano et al, 2013; Rodriguez Celin et al, 2023). Intravenous bisphosphonates have been previously reported to be useful for relieving bone pain in children and adolescents (Rodriguez Celin et al, 2020; Rodriguez Celin et al, 2023), and this was supported from results in this study whereby those people who had received bisphosphonates reported a lower prevalence and intensity of pain.…”
Section: Discussionmentioning
confidence: 96%
See 3 more Smart Citations